“I Didn’t Do That!” Event Valence and Child Age Influence Adults’ Discernment of Preschoolers’ True and False Statements - Johnson, Jonni L. (Journal of interpersonal violence, 2021)
Justice can hinge on adults’ abilities to distinguish accurate from inaccurate child testimony. Yet relatively little is known about factors that affect adults’ abilities to determine the accuracy of children’s eyewitness reports. In this study, adults (N = 108) viewed videoclips of 3- and 5-year-olds answering open-ended and leading questions about positive and negative actually experienced (“true”) events or never experienced (“false”) events that the children either affirmed or denied. Analyses revealed that adults were more accurate at determining the veracity of negative compared with positive incidents, particularly when children said that they had experienced the event. Moreover, adults’ accuracy was at chance for older children’s false denials. Psycholegal implications are discussed.